Le repli des Tunisiens sur le travail indépendant - Bruno, Anne-Sophie (Les chemins de la mobilité : Migrants de Tunisie et marché du travail parisien depuis 1956, 2010)
Keywords: Commerce -- Djerba

‏حتى القبور يا "سين" ترفض الأصغاء - النالوتي, عروسية (قصص من تونس: مختارات قصصية مصدرة بوصف وتحليل وملحقة بمسرد للقصة التونسية, 2010)
Keywords: Littérature

Le débat sur le statut politique des israélites en Algérie et ses acteurs (1870-1943) - Renucci, Florence (Contributions du séminaire sur les administrations coloniales (2009-2010), 2010)
Cette contribution a pour objectif de comprendre quels ont été les débats qui ont porté sur le décret Crémieux entre 1870 et 1943. Ce texte qui imposait la citoyenneté française aux israélites "indigènes" d'Algérie a dans un premier temps été controversé (1870-1939), puis, dans un second temps, abrogé avec le régime de Vichy. L'idée est de comprendre les mécanismes juridico-intellectuels qui sont mis en avant dans ces débats et leur application concrète. Cet article met en évidence la complexité des positionnements des différents acteurs (en particulier du droit) et la difficulté à les classifier.
Keywords: Judaïsme -- Mzab

Mleiha et le peuplement de la péninsule d'Oman à la période Pré-Islamique Récente - Mouton, Michel (Eastern Arabia in the first millenium BC, 2010)
Keywords: Archéologie -- Oman

Continuity and change: Iron Age oasis settlements in Oman - Häser, Jutta (Eastern Arabia in the first millenium BC, 2010)
Keywords: Archéologie -- Oman

L'architecture domestique de l'Age du Fer (1300-300 a.C.) dans la péninsule d'Oman: quelques documents sur les villages et la culture des oasis - Córdoba, JoaquÍn MarÍa (Eastern Arabia in the first millenium BC, 2010)
Keywords: Archéologie -- Oman

An outline of recent discoveries at Salut in the Sultanate of Oman - Avanzini, Alessandra; Phillips, Carl (Eastern Arabia in the first millenium BC, 2010)
Keywords: Archéologie -- Oman

The Iron I-period in South-eastern Arabia - a view from Central Oman - Schreiber, Jürgen (Eastern Arabia in the first millenium BC, 2010)
Keywords: Archéologie -- Oman

Iron Age chronology in South East Arabia and new data from Salut, Sultanate of Oman - Phillips, Carl (Eastern Arabia in the first millenium BC, 2010)
Keywords: Archéologie -- Oman

Jerba à l’épreuve du duel hispano-ottoman - Chater, Khalifa (Des marges aux frontières: Les puissances et les îles en Méditerranée à l’époque moderne, 2010)
jerba a eu, par rapport à la plupart des îles méditerranéennes étudiées par fernand braudel, des conditions spécifiques et une autonomie limitée, puisque sa proximité l’inscrivait dans le prolongement territorial et socio-économique du pays d’appartenance, en dépit de certains traits caractéristiques, identifiés par fernand braudel, qu’elle partageait avec les autres îles méditerranéennes. notre communication se propose ainsi de dégager cette spécificité, en relation avec l’épreuve du duel hispano-ottoman, qui l’a marquée de son empreinte.

Beit el mtoni - The house at the creek - Folkers, Antoni; Smienk, Gerrit (Mtoni - palace, sultan and princess of Zanzibar, 2010)
Keywords: Zanzibar

Architectural family ties - Zanzibar and Oman in the 19th century - Folkers, Antoni; Koopman, Frank (Mtoni - palace, sultan and princess of Zanzibar, 2010)
Keywords: Zanzibar

Unveiling the Past: the Role of Oral History in Understanding Oasis Development - Mershen, Birgit (Oases of Oman : Livelihood Systems at the Crossroads, 2010)

The Architecture of Omani Oases: a Mirror of Social Structures - Korn, Lorenz (Oases of Oman : Livelihood Systems at the Crossroads, 2010)
Keywords: Architecture -- Oman

Historic, Present and Future Role of Livestock on the Al Jabal Al Akhdar Plateau in Northern Oman - Dickhoefer, Uta; Schlecht, Eva (Oases of Oman : Livelihood Systems at the Crossroads, 2010)

Rangeland Vegetation on Al Jabal Al Akhdar — a Key Resource of Oasis Settlement - Brinkmann, Katja; Patzelt, Annette (Oases of Oman : Livelihood Systems at the Crossroads, 2010)

Plant Communities, Endemism and Conservation — History and Heritage - Patzelt, Annette (Oases of Oman : Livelihood Systems at the Crossroads, 2010)
Keywords: Botanique -- Oman

Typology of Oases in Northern Oman - Luedeling, Eike; Buerkert, Andreas (Oases of Oman : Livelihood Systems at the Crossroads, 2010)

Plant Genetic Resources in Oman - Evidence for Millennia of Cultural Exchange in the Middle East - Gebauer, Jens; Khanjari, Sulaiman al-; Buerkert, Andreas; Hammer, Karl (Oases of Oman : Livelihood Systems at the Crossroads, 2010)
Keywords: Botanique -- Oman

From Hunter-Gatherer Communities to Oasis Cultures: Climate Change and Human Adaptation on the Oman Peninsula - Häser, Jutta; Luedeling, Eike; Buerkert, Andreas; Schlecht, Eva (Oases of Oman : Livelihood Systems at the Crossroads, 2010)
Keywords: Archéologie -- Oman

From Balloons to Remotely Controlled Model Planes: Use of High-Resolution Aerial Photography to Document the Status Quo of Omani Oases - Buerkert, Andreas; Schaeper, Wolfgang (Oases of Oman : Livelihood Systems at the Crossroads, 2010)

Integrated Livelihood Systems and Cultural Heritage - Buerkert, Andreas; Schlecht, Eva (Oases of Oman : Livelihood Systems at the Crossroads, 2010)

Il nome di Dio presso i Berberi ibaditi - Brugnatelli, Vermondo (Féch, cun la o cume fuguus: per Romano Broggini in occasione del suo 85o compleanno, gli amici e allievi milanesi, 2010)
Keywords: Linguistique

The Jewel of Muscat: reconstructing A ninth-century sewn-plank boat - Vosmer, Tom (Shipwrecked Tang Treasures and Moonsoon Winds, 2010)
Keywords: Archéologie -- Oman

La formation des réseaux ibadites nord-africaines (VIIIe-XIIe siècle) - Prevost, Virginie (Espaces et réseaux en Méditerranée, VIe-XVIe siècle, 2010)

al-ʿĀdāt wa’l-Taqālīd wa-mā yartabiṭu bihā min ʿAlā’iq Ijtimāʿiyya (Dirāsa Maydāniyya) - Musallimiyya, Shaykha bint Sālim (Shināṣ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Shināṣ Yawmay al-ithnayn wa’l-thulathā’ 11 wa-12 Dhū ‘l-Qaʿda (sic) al-muwāfiq 10 wa-11 Nūfimbir 2008, 2010)
Keywords: Moeurs et coutumes -- Oman

Jughrāfiyyat Wilāyat Shināṣ - Mazrūʿī, Khamīs b. Muḥammad (Shināṣ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Shināṣ Yawmay al-ithnayn wa’l-thulathā’ 11 wa-12 Dhū ‘l-Qaʿda (sic) al-muwāfiq 10 wa-11 Nūfimbir 2008, 2010)
Keywords: Géographie -- Oman

al-Ḥayāt al-Fikriyya li-Wilāyat Shināṣ - Maṭrūshī, Ḥasan b. ʿUbayyid (Shināṣ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Shināṣ Yawmay al-ithnayn wa’l-thulathā’ 11 wa-12 Dhū ‘l-Qaʿda (sic) al-muwāfiq 10 wa-11 Nūfimbir 2008, 2010)
Keywords: Vie intellectuelle -- Oman

al-Maʿālim al-Athariyya li-Wilāyat Shināṣ - Khuzaymī, ʿAbd al-Raḥmān b. ʿĀmir (Shināṣ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Shināṣ Yawmay al-ithnayn wa’l-thulathā’ 11 wa-12 Dhū ‘l-Qaʿda (sic) al-muwāfiq 10 wa-11 Nūfimbir 2008, 2010)
Keywords: Archéologie -- Oman

Shināṣ fī ʿAṣr al-Nahḍa - Hāshimī, Hind bint ʿAbdallāh (Shināṣ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Shināṣ Yawmay al-ithnayn wa’l-thulathā’ 11 wa-12 Dhū ‘l-Qaʿda (sic) al-muwāfiq 10 wa-11 Nūfimbir 2008, 2010)

al-Makāna al-Tārīkhiyya li-Wilāyat Shināṣ - Daramkī, Sayf b. Muḥammad (Shināṣ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Shināṣ Yawmay al-ithnayn wa’l-thulathā’ 11 wa-12 Dhū ‘l-Qaʿda (sic) al-muwāfiq 10 wa-11 Nūfimbir 2008, 2010)
Keywords: Oman -- Histoire

al-Makāna al-Tārīkhiyya li-Wilāyat al-Muḍaybī - Ẓafrī, Saʿīd b. Sulaymān b. Subayḥ al- (al-Muḍaybī ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat al-Muḍaybī Yawmay al-Aḥad wa’l-Ithnayn 21 wa-22 Dhū ‘l-Ḥijja al-muwāfiq 30 wa-31 Dīsimbir 2007, 2010)
Keywords: Oman -- Histoire

al-Muḍaybī fī ʿAṣr al-Nahḍa - Rāshidī, Mubārak b. ʿAbdallāh al- (al-Muḍaybī ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat al-Muḍaybī Yawmay al-Aḥad wa’l-Ithnayn 21 wa-22 Dhū ‘l-Ḥijja al-muwāfiq 30 wa-31 Dīsimbir 2007, 2010)

al-Maʿālim al-Athariyya wa-Madà Ta’thīrihā ʿalà ‘l-Khāriṭa al-Siyāḥiyya - Jābirī, Sulaymān b. Saʿūd b. ʿAlī al- (al-Muḍaybī ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat al-Muḍaybī Yawmay al-Aḥad wa’l-Ithnayn 21 wa-22 Dhū ‘l-Ḥijja al-muwāfiq 30 wa-31 Dīsimbir 2007, 2010)
Keywords: Archéologie -- Oman

al-Mawrūth al-Shaʿbī fī Wilāyat al-Muḍaybī - Hāshimī, Saʿīd b. Muḥammad b. Saʿīd al- (al-Muḍaybī ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat al-Muḍaybī Yawmay al-Aḥad wa’l-Ithnayn 21 wa-22 Dhū ‘l-Ḥijja al-muwāfiq 30 wa-31 Dīsimbir 2007, 2010)
Keywords: Moeurs et coutumes -- Oman

al-Ḥayāt al-Fikriyya bi-Wilāyat al-Muḍaybī qadīman wa-ḥadīthan - Būsaʿīdī, Ṣāliḥ b. Aḥmad b. Sayf al- (al-Muḍaybī ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat al-Muḍaybī Yawmay al-Aḥad wa’l-Ithnayn 21 wa-22 Dhū ‘l-Ḥijja al-muwāfiq 30 wa-31 Dīsimbir 2007, 2010)
Keywords: Vie intellectuelle -- Oman

Jughrāfiyyat Wilāyat al-Muḍaybī - Balūshī, Ibrāhīm b. Ḥasan al- (al-Muḍaybī ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat al-Muḍaybī Yawmay al-Aḥad wa’l-Ithnayn 21 wa-22 Dhū ‘l-Ḥijja al-muwāfiq 30 wa-31 Dīsimbir 2007, 2010)
Keywords: Géographie -- Oman

مدينة القيروان زمن ثورة أبي يزيد الخارجي (النقود كشاهد) - الغضبان, محمد بن الحبيب بن محمد (أعمال ندوة موقع القيروان في الثقافة الإسلامية من تاريخ التأسيس إلى اليوم - الدين والأدب, 2010)
وهكذا يبدو أن أبا يزيد كان فعلا يضرب مسكوكاته وهو بالقيروان فقط. فكلما كان موجودا بها ويشرف على إدارتها إلا وضربت نقود تحمل تاريخ سيطرته عليها إلى جانب اسمها. لكنه عندما خسر المدينة فعلا منذ أواخر شوال 334 هـ لم تعرف له نقود بعد ذلك. لقد كانت القيروان هي الفكرة الأولى في ثورته ومن أجلها ومن أجل ما ضمته بين أسوارها من تاريخ وشرعية وقدسية وعلماء مالكيين... ضرب باسمها النقود ليستميل كل ما حوته من معان وقيم وحاضر ملموس آنذاك. وانتهت ثورة أبي يزيد وانتهت دولته التي لم تعمر كثيرا لكن بقي لنا ما يخبر عنها من شواهد مادية تمثلت في نظام نقدي متميز لم يكن له مثيل من قبل ومن بعد في افريقية في محتواه النصي الإيديولوجي. وباعتماد النصوص الإخبارية ومقارعتها ببعضها البعض، ثم إضافة معطيات النقود التي ضربها أبو يزيد إليها أمكن تحديد الأوقات التي يمكن أن يكون اختارها الثائر لإصدار نقوده. هذا وكان هاجس الدعاية للثورة ومبادئها المعلنة هو من أهم الأسباب المفسرة لها ولاختيار نصوصها الموجهة بكل دقة لأهالي افريقية السنة عموما والقيروان خصوصا، ولأنصار الثورة الخوارج. ومما يثبت ما للقيروان من مكانة كبيرة في وجدان السكان حاولت أن تستثمرها مختلف القوى بإفريقية أن الخليفة المنصور لدين الله ضرب دينارا باسم القيروان سنة 334 هـ عندما طرد سكانها أبا يزيد. فقد اعتمد نفس السياسة الدعائية الموجهة لكسب نصرة الأهالي مجددا ضد أبي يزيد. وقد اثبت كل ذلك ما للمدينة من دور في نجاح أو فشل المشاريع السياسية الثورية والرسمية على حذ السواء. ورغم أن المنصور بالله لم يختر القيروان مقر سكناه بعد القضاء على الثورة، إلا أنه بنى بالقرب منها مدينة غير بعيدة (ميل ونصف تقريبا) متصلة بها تعتبر امتدادا لها. وربما كان قراره ذلك يرمي إلى إنشاء مركز سياسي وعسكري يراقب به المدينة عن قرب تفاديا لمحاولة أخرى شبيهة بثورة أبي يزيد.
Keywords: Ibn Kaydad; Kharijisme

La migration des Juifs du Garbum en Sicile (1239) - Mandala, Giuseppe (Maghreb-Italie: des passeurs médiévaux à l'orientalisme moderne, XIIIe-milieu XXe siècle, 2010)
Keywords: Judaïsme -- Djerba

Time, place and Memory: songs for an African Jewish Pilgrimage - Davis, Ruth Frances (Music and Displacement: Diasporas, Mobilities, and Dislocations in Europe and Beyond, 2010)
Keywords: Judaïsme -- Djerba

Le pèlerinage "Lag ba Omer" à Djerba (Tunisie): une forme de migration touristique - Conord, Sylvaine (Socio-anthropologie de l’image au maghreb, 2010)
Keywords: Judaïsme -- Djerba